THE RELATIONSHIP BETWEEN NURSES’ THERAPEUTIC COMMUNICATION AND THE IMPLEMENTATION OF PATIENT EDUCATION FOR DIABETES MELLITUS AT BEKASI DISTRICT HOSPITAL IN 2025 - Arabta M. Peraten Pelawi; Syfa Alivia Salmabila; Sofi Nurul Aulia; Siti Aminah; Meliyana, Ernauli (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: Diabetes mellitus is a chronic condition that necessitates long-term care and continual education to enable individuals to take the best possible care of themselves. In order to effectively provide instruction through therapeutic communication, nurses are essential. Patients’ comprehension, compliance, and capacity to control their illness can all be enhanced by effective therapeutic communication. Methods: A cross-sectional design was employed in this investigation. Patients with diabetes mellitus at RSUD Kabupaten Bekasi made up the study’s population. Purposive sampling was used to pick 117 respondents for the sample. Questionnaires on nurses’ therapeutic communication and patient education implementation were utilized as research tools. The Chi Square test was used for both univariate and bivariate analysis of the data at a significance level of 0.05. Results: According to the findings, the majority of nurses’ therapeutic communication fell into two categories: adequate (44 respondents, 37.6%) and good (73 respondents, 62.4%). Patient education for diabetes mellitus was mostly implemented in three categories: sufficient (61 respondents, 52.1%), good (54 respondents, 46.2%), and poor (2 respondents, 1.7%). The results of the Chi-Square test showed a significant correlation between the implementation of education for patients with diabetes mellitus at RSU Kabupaten Bekasi in 2025 and the therapeutic communication of nurses, with a p-value of 0.003 (<0.05). Conclusions: The implementation of education for patients with diabetes mellitus at RSUD Kabupaten Bekasi is significantly correlated with the therapeutic communication skills of nurses. The more effectively nurses communicate therapeutically, the more effectively patient education is implemented. It is anticipated that improved patient comprehension, therapy adherence, and nursing service quality will result from effective therapeutic communication.